Biblical Theology Appropriately Postmodern - Brueggemann, Walter (Biblical theology bulletin, 1997)
We are at the end of Christian interpretive hegemony with its seemingly inevitable adjunct of supersessionism. This opens the way for fresh approaches and perhaps fresh interactions between Jewish and Christian interpretive practices that need not be, respectively, aggressive or defensive. This also allows acknowledgment that the text itself is profoundly polyvalent, that the Subject of theological interpretation is endlessly and irascibly elusive, and that every interpretive effort is local and provisional. This implies that interpreters recognize that interpretations other than my own (or of my interpretive community) may be equally appropriate, and must be taken seriously in my (our) own work.